Effectiveness of simulation in psychiatry for initial and continuing training of healthcare professionals: protocol for a systematic review - Piot, Marie-Aude (BMJ Open, 2018)
INTRODUCTION: Although most healthcare professionals must deal with patients with mental illness, many are not prepared for the various situations that can ensue. Simulation may be a powerful pedagogical tool for simultaneously teaching knowledge, skills and attitudes. We aim to assess the effectiveness of simulation for initial and continuous training in psychiatry for healthcare professionals. METHODS AND ANALYSIS: A comprehensive search for randomised and non-randomised controlled studies and single-group pretest/post-test reports will be conducted in electronic databases including MEDLINE, EMBASE, Scopus, CINAHL, PsychINFO, ERIC, the Cochrane Central Register of Controlled Trials (CENTRAL) and the Web of Science (Science and Social Sciences Citation Index), with a detailed query. The reference lists of selected studies, key journals and trial registers will also be searched for additional studies. Two independent reviewers, following predefined inclusion criteria, will screen titles and abstracts first and then the full texts of the remaining articles. A third author will evaluate discrepancies to reach a consensus. It will include randomised controlled trial (RCT), non-RCT, pre-test/post-test design studies, post-test design for satisfaction evaluation and qualitative studies. Risk of bias will be assessed by using the Cochrane Collaboration Tool for assessing risk of bias in RCTs. Meta-analyses will be performed if we find sufficient studies that assess predefined outcomes and if their characteristics are not too different. The quality of evidence will be assessed by the Grading of Recommendations Assessment, Development and Evaluation. A narrative synthesis will be performed for qualitative studies and when meta-analyses are deemed not possible. ETHICS AND DISSEMINATION: Ethics permission is not required. Dissemination will be through publication in peer-reviewed journals, national and international conferences, and the lead author’s doctoral dissertation. TRIAL REGISTRATION NUMBER: CRD42017078779.